SPECIFIC ASPECTS OF DIAGNOSIS IN CASES OF MECHANICAL JAUNDICE ACCOMPANIED BY LIVER CIRRHOSIS - Kenjaev Laziz Razzokovich, Urokov Shukhrat Tukhtaevich (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Cirrhosis of the liver (LC) remains one of the most pressing medical problems to date due to its significant increase in incidence and high mortality.The aim of the research was to study the specific aspects of the clinical course of the disease in patients with concomitant liver cirrhosis and mechanical jaundice.This article presents the results of a study of 66 patients with mechanical jaundice caused by gallstone disease, concomitant with cirrhosis of the liver (LC).All patients were divided into 2 groups: the first group included 46 patients with mechanical jaundice with LC, and the second - only 20 patients with mechanical jaundice.Mechanicaljaundice in 64% of patients was caused by cholelithiasis treated in this surgical clinic, of which 20.4% of them were identified as concomitant diseases with various stages of liver cirrhosis.Compared were the complaints of patients of both groups, the clinical course, the results of objective observation, laboratory research, the results of additional instrumental examination and their specificity.In cases of mechanical jaundice and chronic diffuse liver disease, mechanical jaundice is the first treatment, which is an effective treatment to ensure bile movement in the biliary system, general bile duct permeability through the endoscope. This minimally invasive treatment simultaneously reduces the activity of both mechanical jaundice and chronic diffuse diseases of the liver tissue.